The Effectiveness of Schema Therapy and Mindfulness on Psychological Distress in Patients with Rheumatoid Arthritis - Shad, Saeid; Ghasemi Motlagh, Mehdi; Bakhshipour , Abolfazal (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to determine the effectiveness of schema therapy and mindfulness on psychological distress in patients with rheumatoid arthritis in Mashhad in 2025. The present study employed a quasi-experimental pretest–posttest design with a control group. A total of 45 patients with rheumatoid arthritis who met the inclusion criteria were selected through purposive sampling and were randomly assigned to the study groups. The Kessler Psychological Distress Scale (2003) was used for assessment. Schema therapy was implemented based on the model of Riso et al. (2008), and group mindfulness was conducted based on the therapeutic program developed by Teasdale, Williams, and Segal (2018). Data were analyzed using inferential statistical indices, including repeated-measures analysis of variance, multivariate analysis of covariance, and one-way analyses of covariance within the MANCOVA framework. The effectiveness of schema therapy and mindfulness on psychological distress in patients with rheumatoid arthritis was sustained (p < .05). However, no difference was observed between schema therapy and mindfulness in terms of their effectiveness. Group schema therapy and mindfulness can be used to reduce psychological distress in patients with rheumatoid arthritis and may partially alleviate the pain and suffering experienced by these patients.